2009
DOI: 10.1530/eje-08-0596
|View full text |Cite
|
Sign up to set email alerts
|

Impaired islet turnover in human donor pancreata with aging

Abstract: Objective: The prevalence of type 2 diabetes mellitus escalates with aging although b-cell mass, a primary parameter of b-cell function, is subject to compensatory regulation. So far it is unclear whether the proliferative capacity of pancreatic islets is restricted by senescence. Materials and methods: Human pancreatic tissue from nZ20 non-diabetic organ donors with a mean age of 50.2G3.5 years (range 7-66 years) and mean body mass index of 25.7G0.9 kg/m 2 (17.2-33.1 kg/m 2 ) was morphometrically analyzed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
1
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(82 citation statements)
references
References 35 publications
4
74
1
3
Order By: Relevance
“…Evidence for an age-related decrease in an adaptive proliferative response in islets of mice >2 months old has been described [39]. Similarly, in human organ donors, an age-related decrease of replicating cells has been interpreted as evidence of decreased adaptability [48]. These data taken together suggest that, whereas the population of islet cells is established and not plastic in man after about age 20 years, this point is reached in mice at approximately 1 year; adaptability of young mice to obesity, pregnancy and pancreatic damage may model the potential plasticity of human islets in individuals <20 years of age and not the relatively stable condition in adults.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence for an age-related decrease in an adaptive proliferative response in islets of mice >2 months old has been described [39]. Similarly, in human organ donors, an age-related decrease of replicating cells has been interpreted as evidence of decreased adaptability [48]. These data taken together suggest that, whereas the population of islet cells is established and not plastic in man after about age 20 years, this point is reached in mice at approximately 1 year; adaptability of young mice to obesity, pregnancy and pancreatic damage may model the potential plasticity of human islets in individuals <20 years of age and not the relatively stable condition in adults.…”
Section: Discussionmentioning
confidence: 99%
“…However, the apoptotic rate has been reported to be increased in obese and diabetic individuals compared with the rate in lean and non-diabetic groups [123]. In contrast, a study by Reers et al showed that a decline in beta cell replication with age was not associated with a change in the frequency of apoptosis [124]. The increase in the apoptotic rate has been explained, in part, by the accumulation of amyloid plaques [125], aggregates of islet amyloid polypeptide (IAPP, a hormone co-secreted with insulin), which are increased in islets of diabetic and obese non-diabetic individuals.…”
Section: Old Agementioning
confidence: 91%
“…In adults, the frequencies reported are in the range of 0.4-0.6% insulin-positive duct cells whether in organ donors or autopsied pancreas, although in some pancreata no insulin-positive cells were detectable [58,69,71,72]. The dynamic nature of these insulin-positive cells is suggested by their increase seen in pancreas organs from obese patients [71,72], in patients with chronic pancreatitis [73] during pregnancy [74], and in patients receiving partial pancreatectomy due to recurrent hypoglycemia 1-2 years after gastric bypass [75].…”
Section: Evidence Of Compensatory Expansion In the Adult Human Pancreasmentioning
confidence: 98%
“…However, this low level of detection may result from the tissue being only retrieved after death. In a recent study on human organ donor pancreata, all pancreata had Ki67 + β-cells, with a stable, albeit low, percentage in donors from 40 to 65 years of age [69]. In another study, donor pancreata had little or no Ki67 + insulin-positive cells, but grafts of isolated islets from such donors had 0.22 ± 0.03% Ki67 + insulinpositive cells after 4 week transplantation in immunocompromised normoglycemic mice; this level was also found in frozen human pancreas obtained at surgery [70].…”
Section: Evidence Of Compensatory Expansion In the Adult Human Pancreasmentioning
confidence: 99%